REPRESSION OF THE NATION'S SELF-SACRIFICE - Allayarov Abdumalik (Journals Park Publishing, 2025)
In this article, the author analyzes and highlights the life path of the poet Usman Nasir, his brilliant activity in the creative world, years of exile and repression based on written sources and scientific literature.
Keywords: Usman Nasyr, disease, captivity, poetry, people's retreat, collection, poetic epic.